A Critique of the Principles of Empiricism in Humanities - Ali Mesbah (حکمت اسرا, 2012)
“Empiricism” as the first approach in the humanities, attracted the attention of the scholars of this area, and in spite of the criticisms and serious rivals, is still predominant in the scholarships relevant to the humanities and social sciences. Adherents and opponents of empiricism in the humanities have made use of various approaches and ways to prove their own views and to refute the arguments of the opponents: from a shift in the subject of humanities to the progress in their goals and to the transformation of their ontological and epistemological bases. A key point overlooked by the critics of empiricism in humanities, seems to be the investigation of the nature of the subject of humanities and its methodological implications. Paying attention to this point can reveal a number of the shortcomings of empiricism. The point of departure of this article is the methodological principle that the method of each science is related to its subject, and it is the nature of the subject that determines the appropriate research method. Accordingly, it tries to analyze the nature of the subject of the humanities and to show that it does not fit the empirical method. The approach of this study is logical analysis of the notions employed in the subjects of the questions of humanities in order to illustrate that these issues include such concepts as primary intelligibles, logical secondary intelligibles, and imaginary mental matters (iÝtibÁrÐyyÁt), the study of each of which needs a specific and unique method. Hence, the suggestion of the present article is that although the empirical method, in the study of some of the subjects of humanities has its own appropriate and limited efficiency, it cannot be considered and emphasized as the only helpful and favorable method; but, a significant part of the questions of the humanities involves other ways in order to be able to explore all of their subjects and achieve their goals.